2003
DOI: 10.1021/jo005774c
|View full text |Cite
|
Sign up to set email alerts
|

Direct Amination of 1-Substituted 3,5-Dinitrobenzenes by 1,1,1-Trimethylhydrazinium Iodide

Abstract: The amination of 1-X-3,5-dinitrobenzenes via the vicarious nucleophilic substitution of hydrogen (VNS) with 1,1,1-trimethylhydrazinium iodide (TMHI) in the presence of t-BuOK or NaOMe in DMSO was studied. It was observed (when X = OMe, OCH(2)CF(3), OCH(2)CF(2)CF(2)H, OPh) that the amination occurs regioselectively (ratio of ortho/para-isomers is approximately 9:1) and with high yield. For X = SPh or SCH(2)Ph, the reaction proceeded with a low yield (less than 20%), with a ratio of ortho/para-isomers approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Hydrogenation of trinitrotoluene (TNT) in recent years becomes a reaction of practical importance for utilization of nitroaromatic explosives to useful chemicals (dyes, amino compounds, etc.) [11,12]. Platinum metals catalyze selective reduction of nitroaromatic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenation of trinitrotoluene (TNT) in recent years becomes a reaction of practical importance for utilization of nitroaromatic explosives to useful chemicals (dyes, amino compounds, etc.) [11,12]. Platinum metals catalyze selective reduction of nitroaromatic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…These effective amination reagents are hydroxylamine [3], 1,1,1-trimethylhydrazinium iodide (TMHI) [4][5][6], 4-amino- [7,8] or 4-alkylamino-1,2,4-triazoles [9] and sulfenamides [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…meta-Substituted arenes are formed most readily by replacement of a halogen atom (Cl, Br, I) in copper-and palladium-catalyzed reactions [10] or of another readily departing group (such as nitro group or fluorine atom) by nucleophilic species generated in situ [11][12][13]. Systematic studies on such reactions were initiated relatively recently [11-13] due to wide prospects in further functionalization of the substrates [11,14].Studies on the kinetics of nucleophilic replacement in meta-substituted nitrobenzenes by the action of phenols in the presence of potassium carbonate have shown that the dependences of the rate constant on the temperature, reagent nature, and nucleofugality of the leaving group differ considerably [12,13,15,16] from those found for analogous reactions with potassium phenoxides [17][18][19][20]. With the goal of elucidating the general relations between the reactant structure and energy parameters of the reaction, which provide some information on the reaction mechanism, we studied the relative mobilities of the nitro group in 1,3-dinitrobenzene (I) and fluorine atom in 1-fluoro-3-nitrobenzene (II) in reactions with phenols III-VI in DMF in the presence of potassium carbonate (Scheme 1) at different temperatures.…”
mentioning
confidence: 99%
“…meta-Substituted arenes are formed most readily by replacement of a halogen atom (Cl, Br, I) in copper-and palladium-catalyzed reactions [10] or of another readily departing group (such as nitro group or fluorine atom) by nucleophilic species generated in situ [11][12][13]. Systematic studies on such reactions were initiated relatively recently [11][12][13] due to wide prospects in further functionalization of the substrates [11,14].…”
mentioning
confidence: 99%